Răspuns :
x(1+3+5+.......+59)=5400
seria 1+3+5......+2n-1=n*n
59=2n-1
n=30
x*30*30=5400
x*900=5400
x=5400/900
x=6
seria 1+3+5......+2n-1=n*n
59=2n-1
n=30
x*30*30=5400
x*900=5400
x=5400/900
x=6
x(1 + 3 + 5 + 7 ....... + 59) = 5400
x(59 + 1)[(59 - 1) : 2 + 1] : 2 = 5400
x * 60 * [58 : 2 + 1] : 2 = 5400 | : 60
x * [29 + 1] : 2 = 90
x * 30 : 2 = 90 | : 30
x : 2 = 3
x = 2 * 3
x = 6
x(59 + 1)[(59 - 1) : 2 + 1] : 2 = 5400
x * 60 * [58 : 2 + 1] : 2 = 5400 | : 60
x * [29 + 1] : 2 = 90
x * 30 : 2 = 90 | : 30
x : 2 = 3
x = 2 * 3
x = 6